Assessment of Chitosan/Gelatin Blend Enriched with Natural Antioxidants for Antioxidant Packaging of Fish Oil - Mia Kurek; Mario Ščetar; Marko Nuskol; Tibor Janči; Marija Tanksoić; Damir Klepac; Mojca Čakić Semenčić; Kata Galić (MDPI AG, 2024)
In this research, bio-based films were developed using polyelectrolyte complexes derived from chitosan and gelatin for packaging fish oil. To further enhance the antioxidant functionality, the films were enriched with gallic acid and orange essential oils, either individually or in combination. Initially, the films were characterized for their physico-chemical, optical, surface, and barrier properties. Subsequently, the phenolic compounds and antioxidant capacity of the films were assessed. Finally, the films were tested as antioxidant cover lids for packaging fish oil, which was then stored at ambient temperature for 30 days, with periodical monitoring of oil oxidation parameters. This study revealed that the inclusion of gallic acid-induced possible crosslinking effects, as evidenced by changes in moisture content, solubility, and liquid absorption. Additionally, shifts in the FTIR spectral bands suggested the binding of gallic acid and/or phenols in orange essential oils to CSGEL polymer chains, with noticeable alterations in film coloration. Notably, films containing gallic acid exhibited enhanced UV barrier properties crucial for preserving UV-degradable food compounds. Moreover, formulations with gallic acid demonstrated decreased water vapor permeability, while samples containing orange essential oils had lower CO2 permeability levels. Importantly, formulations containing both gallic acid and essential oils showed a synergistic effect and a significant antioxidant capacity, with remarkable DPPH inhibition rates of up to 88%. During the 30-day storage period, fish oil experienced progressive oxidation, as indicated by an increase in the K232 value in control samples. However, films incorporating gallic acid or orange essential oils as active antioxidants, even used as indirect food contact, effectively delayed the oxidation, highlighting their protective benefits. This study underscores the potential of sustainable bio-based films as natural antioxidant packaging for edible fish oil or fresh fish, offering a promising tool for enhancing food preservation while reducing its waste.